EFL Teachers Perceptions of Mobile Device Use in Oman: Regulatory Considerations and Differences Across Gender and Experience - Al-Mamari, Zainab Hamed Khalid; Al-Mekhlafi, Abdo Mohamed (Universitas Pasundan, 2026)
This descriptive study explores the perceptions of EFL teachers in Omani Cycle 2 schools regarding the use of mobile devices in English language teaching. The sample consisted of 91 male and female teachers, and data were collected using a survey questionnaire. The findings revealed that teachers generally held positive views toward integrating mobile devices into English classrooms and supported the establishment of regulatory practices to guide their use. The results also showed no statistically significant differences in teachers’ perceptions based on gender or years of experience. Additionally, the study identified a general consensus regarding the anticipated challenges associated with mobile device use. The findings further highlighted strong agreement among teachers on the importance of ethical considerations and the need for clear policies governing the use of mobile technologies in the classroom. The paper concludes with implications and recommendations for effective mobile device integration in English language teaching.